O papel do interdiscurso, da cenografia e do ethos na constituição do discurso literário de Machado de Assis - Pinto, Flávio Sabino (2013)
This thesis has as its theme the examination of discourses of Machado de Assis, from the perspective of discourse analysis of the French line. It is not intended to address the literature as an aesthetic object, but as a producer of discourse, that is in and through language. Therefore, is necessary to observe the socio-historical conditions, to situate the speeches included in the analysis. It appears that these speeches are part of one of the files most famous in Brazil, it has been disclosed and published in major media such as theater, music and television for its importance in literature and especially in the portuguese language. When relating Discourse Analysis and literature, becomes possible to analyze the processes of discursive formation, selected from the corpus, consisting of twelve speeches by Machado de Assis, published at the time of the Brazilian literary realism. To realize our goals we seek contributions from Dominique Maingueneau on the conditions of production of literary discourse. At the inquest to investigate how to build the file of selected speeches by Machado de Assis, there is the role of interdiscourse as a fundamental category for the formation of memory of literary discourse. Are investigated, especially the discursive construction of the file, it takes the speaker to build the most essential themes of humanity, such as the role of the set design, which contributes effectively in the construction and organization of discourse. As the archive of literary discourse also constructed by discursive ethos, is necessary to observe how the ethos operationalizes the identity formation of discourse. We conclude that the study of the files of selected speeches reveals the importance of integrating Linguistica understanding of literature as an updated approach, in that it expands and enhances the understanding of this relationship